Efeitos da deleção de REST do músculo esquelético sobre a composição corporal e função muscular de camundongos c57bl/6 - Canevazzi, Gustavo Henrique Rigo (Universidade Federal de São Carlos, 2018)
In order to elucidate the role of skeletal muscle REST (RE1 Silencing Transcription Factor) protein on body composition and muscle functionality, we aimed at evaluating the effects of the specific deletion of REST from skeletal muscle (REST MKO) on mouse morphology, in vivo muscle strength and locomotor activity, and in vitro mechanical properties of isolated fast and slow skeletal muscles. Twenty-five mice were used in our study: 12 wild type (WT; 6 males and 6 females) and 13 REST MKO (8 males and 5 females). After 2 weeks of acclimation, the animals were housed in cages mounted with a running wheel (Day 0) so as to assess the level of voluntary physical activity. Subsequently (Day 4), the animals returned to standard cages and 3 days later (Day 7) grip strength and body composition were assessed. Euthanasia was carried out in the following two to four days (Days 9, 10 and 11; n = 2-4 mice/day) during which slow-twitch soleus (SOL) and fast-twitch extensor digitorum longus (EDL) muscles were collected to assess their mechanical properties during electrical-stimulation protocols. No statistical differences between REST MKO and WT mice were found in female mice. Based on this observation, only the data obtained in male mice were used. REST MKO had no significant effect on body weight, relative grip strength and voluntary physical activity; however, it increased fat (+9%) and decreased lean (-9%) masses significantly. Muscle relative weight was 31% higher in SOL and 19% smaller in the EDL of the REST MKO as compared to WT group (both p<0,05). Evaluation of isolated skeletal muscles mechanical properties during electrostimulation protocols indicated that REST MKO had no effect on maximal relative force in both the SOL and EDL. Regarding the muscle effects, REST MKO promoted greater force development and reduced fatigability in the EDL during the fatigue protocol. In contrast, in SOL muscles the deletion of REST led to a decrease in force production at low frequencies of stimulation and greater fatigue. We have shown that skeletal muscle REST protein seems to be important for the maintenance of lean mass and its loss leads to functional implications in different skeletal muscle tissues.
Effects of skeletal muscle REST deletion on body composition and muscle function in C57BL/6 mice.
Keywords: Rest; Músculo esquelético; Força-frequência; Fadiga; Skeletal muscle; Force-frequency; Fatigue; CIENCIAS BIOLOGICAS::FISIOLOGIA